Fidelity, not adaptation, is essential for implementation - Fixsen, Dean L. (Frontiers in Health Services, 2025)
Fidelity is not yet a requirement when developing an evidence-based innovation or when attempting to use an innovation in typical settings. Currently, users are encouraged to adapt innovations to fit existing practitioner skills and organization situations. Instead of adapting innovations, the essential components of an innovation need to be established in the original research and the essential components need to be used in practice with the support of implementation processes so that promised outcomes can be realized. Fidelity is an assessment of the presence and strength of the essential components that define the independent variable (the innovation) and is directly linked to outcomes. A test of any fidelity assessment is a high correlation (0.70+) with outcomes. The functional relationship between fidelity and outcomes ensures that the essential components are effective and ensures that a reliable fidelity assessment is available. Implementation is the planned process of putting something into effect. Evidence that an innovation has been put into effect is provided by the fidelity assessment. High fidelity scores indicate that the essential components of the innovation are in place and good outcomes are expected. A test of any planned process is fidelity of the use of the innovation. At present fidelity assessments are missing or inadequate and, therefore, there is a notable lack of evidence that an independent variable is present.